The Effect of Financial and Non-Financial Performance on Islamic Social Reporting - Caesara Insan Juniar; Iwan Fakhruddin; Suryo Budi Santoso; Siti Nur Azizah (Indonesian Journal of Business Analytics, 2023)
The development of sharia banking is the reason for the need for disclosure of social responsibility in accordance with sharia principles. This study aims to empirically examine the influence of Profitability, Liquidity, Leverage and Sharia Supervisory Board Size on Islamic Social Reporting in Islamic Commercial Banks in Indonesia registered with the Financial Services Authority (OJK). The theoretical basis used in this research is Legitimacy Theory and Shari'ah Enterprise Theory. This study used a purposive sampling method so that a sample of 11 banks was obtained during the 2017-2021 period. In this study using secondary data and data analysis method used is multiple linear analysis. The research results show that Profitability has a negative and significant effect on Islamic Social Reporting and Liquidity has a positive and significant effect on Islamic Social Reporting . Meanwhile, Leverage and Size of the Sharia Supervisory Board each do not have a significant effect on Islamic Social Reporting.